Intermuscular Adipose Tissue as a Risk Factor for Mortality and Muscle Injury in Critically Ill Patients Affected by COVID-19 - Rossi, Andrea P.; Gottin, Leonardo; Donadello, Katia; Schweiger, Vittorio; Brandimarte, Piero; Zamboni, Giulia A.; Florio, Alessandro; Boetti, Riccardo; Pavan, Gaia; Zamboni, Mauro; Polati, Enrico (Frontiers in Physiology, 2021)
Background: Muscular fatigue and injury are frequently observed in critically ill COVID-19 patients. The aim of this study was to determine whether different muscle adipose tissue depots are associated with mortality and muscle damage in patients affected by COVID-19 admitted to the ICU. Methods: CT images were obtained in 153 ICU patients with COVID-19 (121 males and 32 females). Height, weight, BMI, CRP, CPK, muscle density, and intermuscular adipose tissue (IMAT) were measured. Results: Participants in the highest tertile of IMAT/muscle had the shorter 28-day survival from ICU admission as compared to subjects in the first tertile. Estimates derived from the Cox proportional hazard models, after adjustment for age, sex and BMI, confirmed the results of the survival analysis (HR 3.94, 95%C.I.:1.03-15.09). Participants in the lowest tertile of muscle density had the shorter survival at 28 days from ICU admission as compared to subjects in the highest tertile (HR 3.27, 95%C.I.:1.18-4.61), but the relationship was no longer significant when age was included in the model. Subjects in the second muscle density tertile did not show an increased risk. Participants in the highest tertile of IMAT/muscle and those in the lowest tertile of muscle density showed both significantly higher CPK adjusted for weight values as evaluated during the first 8 days of hospitalization. Conclusion: Our data seem to suggest that higher levels of IMAT/muscle and low muscle density are both associated with higher risk of ICU mortality and muscle injury as evaluated with CPK level.